Leveraging Social Media Information for Small Tourism Enterprises: A Digital Marketing Framework Approach in Arusha Municipality, Tanzania. - Mbura, Omari Khalifa; Massawe , Donatus Peter; Tumsifu, Elly (University of Dar es Salaam Library Journal, 2024)
The use of social media allows people and businesses to share information in various forms such as through pictures, videos, and messages online, and has been expanding to a larger audience in the past 10 years. This study attempts to bridge a gap by examining the relationship between social media use and Small Tourism Enterprises’ marketing performance in Tanzania’s tourist city, Arusha. A self-administered structured questionnaire was used in data collection where 133 Small Tourism Enterprises were part of our unit of analysis participating in this study. Using a cross-sectional survey design, quantitative data were collected and analysed using Partial Least Squares Structural Equation Modelling with the aid of Smart-PLS3 software. The study revealed that the five stages of the Digital Marketing Framework (DMF) influence the Marketing Performances of Small Tourism Enterprises based on attracting, engaging, retaining, and learning about customers. The adoption and exploitation of DMF by Small Tourism Enterprises have managed to increase customer acquisition level, have customer retention, they have increased their sales and profitability also the product demand has been improved extensively. This research contributes immensely to theory, management, and methodology because the adoption and engaging DMF based on the use of SM creates performance in marketing offerings from Small Tourism Enterprises in developing countries like Tanzania. Keywords: Social Media Information, Small Tourism Enterprises, Digital Marketing Framework, Performance https://dx.doi.org/10.4314/udslj.v19i2.9